Authors’ response: it’s time to consider integrating the degree of pulmonary fissure completeness into a morbidity risk scoring system for video-assisted thoracoscopic pulmonary resections - Li, Shuangjiang; Che, Guowei (Journal of Thoracic Disease, 2018)
We would like to appreciate Dr. Hishida (1), Dr. Lococo with his colleagues (2) and Dr. Lee with his colleagues (3) for their interests and positive comments regarding to our recent single-center retrospective study addressing on the significance of degree of pulmonary fissure completeness (PFC) in video-assisted thoracoscopic surgery (VATS) lobectomy for non-small-cell lung cancer (NSCLC) (4). Meanwhile, we would also like to thank Dr. Laura Chiara Guglielmetti, the Section Editor of the Journal of Thoracic Disease, for her commission to invite the three professionals in the specialty of thoracic surgery to contribute their great editorials on our work.